Pengaruh Persepsi Siswa tentang Kinerja Guru terhadap Kemampuan Pemecahan Masalah Matematis - Dyah Arum Puspanaja; Inka Mayelda Putri; Achi Rinaldi (Journal on Education, 2024)
This reseacrh aims to examine whether students' perceptions of teacher performance have a positive influence on their mathematical problem-solving abilities. The research subjects consisted of 30 tenth-grade students from SMKN 3 Bandar Lampung. The research methodology employed is a quantitative approach with data analysis techniques, including regression analysis, within the framework of an ex-post facto study. The research instruments include a problem-solving ability test comprising four items that have undergone validity testing, reliability testing, difficulty level testing, and discrimination power testing. Additionally, a student perception questionnaire regarding teacher performance was utilized, consisting of 25 statement scales adopted from Suryanti (2021) with indicators such as teaching style, ability to interact with students, and personal characteristics. The findings indicate that students' perceptions of teacher performance do not significantly influence their mathematical problem-solving abilities. There is a possibility of other factors, such as family support, learning environment, or teaching methods, not accounted for in this study. Each student responds uniquely to mathematical challenges, suggesting that the influence of teacher performance may vary among individuals and requires further consideration. The results highlight the significance of other elements beyond teacher performance in developing students' mathematical problem-solving abilities. Educators and researchers can explore these factors for a more comprehensive understanding, taking into account the relevance of the findings in specific learning contexts and student characteristics. Although no significant influence was detected, practical implications include efforts to enhance other factors supporting students' mathematical abilities, such as the development of additional teaching strategies or increased support outside the classroom.